Anterior chevron-type tibial osteotomy for treatment of osteochondral lesion of the talus using osteochondral autograft transfer system: A case report and technical description - Cândido Nishikawa, Danilo Ryuko; Honda Saito, Guilherme; Jardim Fairbanks, Paula; Moreira Mendes, Alberto Abussamra; Aires Duarte, Fernando; Pires Prado, Marcelo (Journal of the Foot & Ankle, 2026)
Introduction: In the osteochondral autograft transfer system (OATS) procedure, a wide accessible area is required to introduce the femoral plug at varying angles. This may not always be achievable through standard anteromedial or anterolateral arthrotomy approaches. The aim of this case report was to describe the use of an anterior chevron-type tibial osteotomy as a technical approach for treating a centrolateral osteochondral lesion of the talus (OLT) with the OATS technique. Methods: A 48-year-old female patient with chronic ankle pain following an ankle sprain 32 years ago. The anterior osteotomy was performed with dimensions of 3 cm in width, 2 cm in depth, and 4 cm in height. After removing the anterior tibial bone block, we identified and debrided the OLT. The lesion site was prepared, and a bone plug obtained from the lateral femoral trochlea was inserted, congruent with the surrounding articular cartilage. The temporarily removed anterior tibial bone block was reattached and secured with three cannulated screws. Results: By 44 months postoperatively, the patient demonstrated significant clinical improvement and had returned to full activity. Preoperatively, she reported a VAS score of 7 for pain, which improved to 1 postoperatively. Her American Orthopaedic Foot and Ankle Society ankle-hindfoot score increased from 41 to 90. Ankle range of motion improved, from a preoperative total of 90 degrees to 100 degrees postoperatively. No complications were observed following the tibial osteotomy or the OATS procedure. Conclusion: The anterior chevron-type tibial osteotomy provided an adequate exposure of a centrolateral OLT, enabling precise graft positioning during the OATS procedure. It allowed safe insertion of the plug at the desired angle while preserving joint congruity. This technique may represent a surgical option for treating centrally and laterally located OLT when conventional approaches do not provide sufficient access.